Implementation of Islamic Education Toward Human and Society - M. Masyrik; Syamsul Aripin (al-Afkar, Journal For Islamic Studies, 2026)
In the context of education, Islam has a broad and comprehensive view of humans and society. Islamic education emphasizes the importance of education as a means to build humans who are noble, knowledgeable, and play an active role in society. This view has its roots in the teachings of Islam which integrate spiritual, moral, intellectual, and social aspects. Education in Islam is not just the transfer of knowledge and science, but also involves the development of strong character and personality. The concept of humans in the Islamic perspective assumes that each individual has unique potential and is given the responsibility to carry out the mandate of Allah SWT. Education becomes a tool to implement and instill universal Islamic values that are relevant to the global context, such as inclusiveness, sustainability, and human and social civilization. The results of this study reveal that the implementation of Islamic education significantly contributes to character building and the strengthening of social values within society. The principles of tawhid, noble character, social responsibility, and the pursuit of knowledge serve as the foundation for nurturing faithful individuals and creating a just and civilized society. This research emphasizes that Islamic education plays a crucial role in fostering collective awareness toward achieving a civil society rooted in moral and spiritual values. The study employs a qualitative library research approach by analyzing relevant literature and previous studies from Islamic education scholars.